Articulações entre a loucura "não-toda" das mulheres, a relação amorosa e o mito de Medéia. - Teixeira, Juliana de Castro (2018)
The main theme of this work is the "not all" madness of women and the love relationship. It follows from the assumption, based on the Lacanian theory, that women have their own madness, which is not the same as the madness in psychosis. This madness is related to the concept of "not all", which is a field not all regulated by the phallic function, from which comes a limitless juissance that affects the way of experiencing love. The term "women", for the purpose of this work, refers to those that occupy the feminine position in the formulas of sexuation proposed by Lacan. Thus, the purpose of this research is to analyze the question of women's "not all" madness in love relationships, based on psychoanalytic literature and Medea myth as the paradigm of this theory. This study is aimed at problematizing the notions of woman, femininity and feminine in Freud and Lacan, in the two moments of his teaching; discuss the love of women in Freud and Lacan; examine the relationship between the female juissance, its singular madness, and love; and identify in the Myth of Media, what it can teach about the feminine riddle, the madness and the way of loving in women. Besides Freud and Lacan, we brought authors who comment on them. Articles were collected from the CNPq and BVS-psi database. It was a theoretical research in psychoanalysis, whose method was a bibliographical review of the psychoanalytic theory and the Medea myth. For that, systematic and deconstructive readings of the collected articles were carried out, which led us to conclude that the women's way of loving is based on erotomania, which can lead to devastation. It is related to the feminine juissance, and in a partnership it can arise when love is no longer able to function, and there remains a merciless jouissance, like the example of Medea, 10 who, upon losing Jason, is capable of the most various follies. Therefore, Medea demonstrates the conditions of a devastated woman. The madness of love lived by Medea highlights what we have daily seen in the current clinical practice.